Udvikling af et klinisk blik: Lokationsbåret praksis i hospitalsregi - Kjær, Malene (Academic Quarter | Akademisk kvarter, 2015)
The article sheds light on a specific practice in the hospital wards: Student nurses developing a clinical professional vision by participating in interactions with patients in clinical settings. Through a multimodal interactional analysis of four short data excerpts the article aims to show how a professional vision is not just learned by being a participant with the patient, but how instruction beforehand and assessment after works together with the practice of participating with the patient. More over the article shows how these three different practices: instruction, participation and assessment takes place in four different locations. It is the claim that the practice of participation and developing a clinical professional vision are shaped not only by different practices in situ but also by the different locations and the affordances these locations have for the interactions taking place.